(untitled) (Scientific journal of the Fergana State University, 2024)
The article reveals the development cycles and phenological characteristics of lepidopteran insects in the agroecosystems of the Fergana Valley. Based on the results of the studies and analyses, it was established that 66 species of lepidopteran insects common in the agroecosystems of the Fergana Valley are characterized by a polyvoltine life cycle, 54 species by a bivoltine life cycle, and 38 species by a monovoltine life cycle. Lepidopteran insects at the adult stage according to flight periods, included in the spring-summer-autumn phenological group, are distinguished by a large number of species (83). At the same time, 6 species belong to the spring, 13 to the summer, 40 species to the spring-summer, 1 species to the autumn, and 15 species to the summer-autumn phenological group. According to the characteristics of wintering, 78 species overwinter at the caterpillar stage, 44 - pupae, 18 - eggs, 2 species in the butterfly state, 5 species in the form of a caterpillar and pupa, 3 species - at the pupa and butterfly stages, and 1 species overwinters at the egg stages, pupae and butterflies.